Marketing Communication Strategies for Consumable Products in Emerging Markets: Insights from Indonesia - Mayendri, Edelwis Tiara Poespa; Ningsi, Tri Wahyu Retno (PT. Sangadji Media Publishing, 2025)
Purpose: This study aims to explore marketing communication strategies for consumable products in emerging markets, with insights drawn from Indonesia’s rapidly evolving digital commerce environment. As competition intensifies in terms of price, product quality, and promotional activities, businesses face growing challenges in developing effective marketing communication approaches that enhance brand positioning and customer engagement. This research seeks to identify key elements and best practices of marketing communication strategies suitable for consumable product sectors operating in highly competitive online marketplaces. Methodology: A qualitative approach was employed, guided by Kotler and Keller’s Integrated Marketing Communication (IMC) framework and P.R. Smith’s SOSTAC model. Data were collected through in-depth interviews and observation of business actors engaged in online commerce in Indonesia, with particular reference to the implementation of marketing strategies on leading e-commerce platforms such as Tokopedia. The study emphasizes the formulation, coordination, and execution of digital marketing communication strategies in a dynamic online retail environment. Findings: The results reveal that successful marketing communication strategies for consumable products in emerging markets involve a combination of advertising, publicity, and interactive digital engagement. Consistent brand messaging across online channels, rapid customer response, and the use of promotional events were identified as crucial factors in strengthening consumer trust and loyalty. The effective integration of IMC components within e-commerce ecosystems supports sustained competitiveness and brand differentiation. Originality/Novelty: This study offers new insights into how integrated marketing communication frameworks can be adapted for consumable product marketing in emerging markets. It highlights the strategic role of e-commerce platforms as adaptive media for digital marketing communication and brand engagement in Indonesia’s dynamic marketplace.